2015
DOI: 10.1002/pts.2126
|View full text |Cite
|
Sign up to set email alerts
|

Development of Films of Novel Polypropylene based Nanomaterials for Food Packaging Application

Abstract: In order to design new antimicrobial nanocomposites with properties for food packaging application, films of polypropylene random copolymer (PPR), PPR/Poly‐β‐pinene (PβP), PPR/clay and PPR/PβP/clay were prepared by melt extrusion. Structural, morphological, mechanical, barrier, antimicrobial properties and thermal stability of the films were determined. PPR and PβP always form a homogeneous system in the amorphous phase; in the binary PPR/clay system, PPR molecules intercalate the clay galleries; in the ternar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Nanomaterials are promising applications of active packaging. In particular, inorganic nanoparticles such as silver, zinc oxide, silicon dioxide, and titanium dioxide nanoparticles are extensively studied, and silver and zinc oxide with antimicrobial functions have already been commercialized in some applications (Ayhan et al, ; Duncan, ). Those nanoparticles are known to be efficient antimicrobial agents because of their unique properties such as high‐temperature stability and low volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials are promising applications of active packaging. In particular, inorganic nanoparticles such as silver, zinc oxide, silicon dioxide, and titanium dioxide nanoparticles are extensively studied, and silver and zinc oxide with antimicrobial functions have already been commercialized in some applications (Ayhan et al, ; Duncan, ). Those nanoparticles are known to be efficient antimicrobial agents because of their unique properties such as high‐temperature stability and low volatility.…”
Section: Introductionmentioning
confidence: 99%
“…It appeared that P β P is more effective on bacteria than yeast and mould for salami especially under vacuum application. The previous study showed that nanomaterial with P β P reduced the test microorganisms ( Escherichia coli ) 24.3% (1.33 log CFU/g) comparing with the control not including P β P …”
Section: Resultsmentioning
confidence: 60%
“…A previous study by Ayhan et al . reported that there is no diffusion of P β P from the material and direct contact with the food is required for a pronounced antibacterial effect …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations